2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319767
|View full text |Cite
|
Sign up to set email alerts
|

Detection of stress/anxiety state from EEG features during video watching

Abstract: This paper studies the effect of stress/anxiety states on EEG signals during video sessions. The levels of arousal and valence that are induced to each subject while watching each video are self rated. These levels are mapped in stress and relaxed states and subjects that fufill criteria of adequate anxiety/stress scale were chosen leading to a subset of 18 subjects. Then, temporal, spectral and non linear EEG features are evaluated for being able to represent accurately states under investigation. Feature sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 17 publications
1
33
2
1
Order By: Relevance
“…For what concerns the EEG, we decided to process the signals provided from the F3 electrode. This choice was due to the fact that, in the literature, prefrontal electrodes are typically considered for the analysis of brain signals concerned with the detection of stress conditions [ 41 , 42 , 43 ]. In order to obtain time series representing the variations in time of the amplitude of the various EEG rhythms, the power spectral density (PSD) was computed on the recorded EEG signals using the periodogram method and quantifying the total power content of the ( –3 ), (3–8 ), (8–12 ) and (12–25 ) frequency bands.…”
Section: Methodsmentioning
confidence: 99%
“…For what concerns the EEG, we decided to process the signals provided from the F3 electrode. This choice was due to the fact that, in the literature, prefrontal electrodes are typically considered for the analysis of brain signals concerned with the detection of stress conditions [ 41 , 42 , 43 ]. In order to obtain time series representing the variations in time of the amplitude of the various EEG rhythms, the power spectral density (PSD) was computed on the recorded EEG signals using the periodogram method and quantifying the total power content of the ( –3 ), (3–8 ), (8–12 ) and (12–25 ) frequency bands.…”
Section: Methodsmentioning
confidence: 99%
“…The electrodes are connected accordingly to the EXG electrodes port based on the international standard positioning system (10-20 system). The electrode port at the EXG Brain Marker device with the universal size standard (DIN Standard) which allowing enabling the use of most available electrodes [11] This device was assembled for the purpose of dynamic data collection whereas the subjects or participant can move along together while completing the given task. In this study, combination and additional device were used.…”
Section: Methodsmentioning
confidence: 99%
“…Stress become very serious health crisis nowadays [4] which lead to affected to public work performance. Currently, most of study in stress were done in psychology area [7], [9], very less study on stress were done in neurophysiological in computational studies using EEG signal [11], [15]. EEG (electroencephalogram) is defined as a graphical representation of the brain's electrical activity and one of the neuroimaging tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found correlations of EEG biomarkers with psychological states that match reports about previous efforts into this direction. It was shown that EEG spectral properties correspond to stress states [32][33][34][35]. However, the exact EEG-frequency range, where this stress response might be found, varies over the full range of frequency bands from delta to gamma across studies.…”
Section: Correlation Of Eeg Biomarkers With Psychological Statesmentioning
confidence: 99%